P20 Description of dietary intakes of acrylamide in the born in Bradford birth cohort study. (16th November 2010) - Hepworth, S J; Fraser, L K; Petherick, E; Burley, V J; Cade, J; de Kok, T; van Breda, S; Kyrtopoulos, S A; Botsivali, M; Kleinjans, J; McKinney, P A
Abstract : Background: Compounds created during the cooking and processing of food may be associated with to future child health if consumed during pregnancy. One such compound is acrylamide, which has been suggested as a potential dietary carcinogen, and is formed during the cooking of starchy foods. Little information is available on intake during pregnancy. Objective: To estimate intakes of the dietary compound acrylamide during pregnancy and describe the association of intakes with maternal age in years (<20, 20–39, 40+), ethnicity and quintile of deprivation when classified using the index of multiple deprivation (IMD07). Design: Data were collected using a Food Frequency Questionnaire (FFQ) within the Born in Bradford multi-ethnic birth cohort study carried out in the city of Bradford, UK. The FFQ was given to all women recruited into Born in Bradford between September 2007 and July 2009 and completed at between 28–32 weeks of pregnancy. Participants were asked to self-complete information on the frequency of intakes for selected food items. Values for acrylamide intake were derived using estimated European exposure values taken from the literature within different food groupings. Values of acrylamide consumption were grouped into quintiles. Multivariate logistic regression was then used to investigate maternal characteristics associated with the highest quintile of acrylamide consumption. Results: 5294 women were recruited between September 2007 and July 2009 and 4212 (79.5%) completed the FFQ. Overall estimated mean intake of acrylamide was 35.5 μg/day (SD: 27.2). French fries (31.1%), toast (18.3%) and crisps (12.2%) made the largest contributions to overall intake levels. Maternal characteristics associated with the highest quintile of acrylamide intake (>52.4 μg/day) was an age less than 20 years old (OR: 2.0, 95% CI 1.6 to 2.5), those aged 40 and over were less likely to be in this quintile (OR: 0.3, 95% CI 0.1 to 0.7) when compared to pregnant women aged 20–39 years. There was a significant interaction between ethnicity and deprivation levels (p=0.01) with pregnant women of white ethnicity showing a increasing trend of being in the highest quintile of intake with increasing deprivation score whereas for women of south Asian ethnicity there was no significant relationship between deprivation and acrylamide intake. Conclusion: Intakes of the dietary contaminant acrylamide during pregnancy were found to vary according to maternal age, ethnicity and deprivation levels. This may have implications for the targeting of public health messages if there are future findings which lead to recommendations for reductions in intake.